Education, lifestyle and life course differences in level of work incapacity – genes and environment. (13th November 2019) - Seglem, K; Torvik, F; Røysamb, E; Gjerde, L C; Magnus, P; Reichborn-Kjennerud, T; Svedberg, P; Ørstavik, R; Vollrath, M
Abstract: Background: As many countries face an aging workforce, it is becoming ever more relevant to understand the underlying causes of work incapacity across the entire working age. Previous twin studies have demonstrated that work incapacity is influenced by genetic as well as environmental factors. Furthermore, educational attainment and lifestyle behaviors are relatively stable from early adulthood and are associated with work incapacity. This association may be confounded by unobserved factors - both genetic and environmental. In two separate twin studies, we examine 1) the stability and change in genetic and environmental factors influencing work incapacity from age 18 until retirement, and sex differences in these effects, and 2) the associations and likelihood of causality between educational attainment, lifestyle and sickness absence. Methods: study 1: A population-based sample of 28, 759 twins were linked to high quality national registry data and followed for up to 23 years. We measured work incapacity as the total proportion of potential workdays lost due to sickness absence, rehabilitation, and disability benefits. study 2: Data from a subsample of 8, 806 twins who completed health questionnaires were linked to registry data on sickness absence and educational attainment. Self-reported lifestyle behaviors were smoking, physical activity and BMI (height and weight). Results: study 1: Structural equation modeling indicated moderate genetic influences on work incapacity throughout life in both men and women, with a high degree of genetic stability from young to old adulthood. study 2: Preliminary regression analyses indicated that genetic factors largely confound the associations between educational attainment, lifestyle and sickness absence. Conclusions: Genetic factors seem to be a major issue in understanding causes of work incapacity. Largely the same genetic factors influence individual differences in work incapacity throughout working age.